2003
DOI: 10.1046/j.1365-2125.2003.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on the pharmacokinetics of multiple‐dose oral voriconazole

Abstract: Aims Voriconazole is a new triazole antifungal agent with activity against a range of clinically important and emerging pathogens. This study determined the effect of food on the pharmacokinetics of voriconazole in healthy volunteers. Methods This was an open, randomized, two-way crossover, multiple-dose study in male volunteers. Twelve subjects received voriconazole 200 mg twice daily for 6.5 days. Each dose was administered either with food or in the fasted state, i.e. not within 2 h of food. Treatment perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(83 citation statements)
references
References 13 publications
0
79
0
4
Order By: Relevance
“…La absorción oral más elevada se obtiene con voriconazol, fármaco que administrado en ayunas alcanza una biodisponibilidad próxima al 100% [25][26][27], cifra que es inferior a su vez en el caso de itraconazol en solución (70%) [21], y que se reduce cuando este fármaco se administra en forma de cápsulas, hasta situarse en el 55%, cifra que es inferior cuando este fármaco se administra junto con una suspensión de alcalinos [18]. La biodisponibilidad de posaconazol, solo comercializado en solución para uso por vía oral, se sitúa en torno al 60% [10].…”
Section: Características Farmacocinéticasunclassified
“…La absorción oral más elevada se obtiene con voriconazol, fármaco que administrado en ayunas alcanza una biodisponibilidad próxima al 100% [25][26][27], cifra que es inferior a su vez en el caso de itraconazol en solución (70%) [21], y que se reduce cuando este fármaco se administra en forma de cápsulas, hasta situarse en el 55%, cifra que es inferior cuando este fármaco se administra junto con una suspensión de alcalinos [18]. La biodisponibilidad de posaconazol, solo comercializado en solución para uso por vía oral, se sitúa en torno al 60% [10].…”
Section: Características Farmacocinéticasunclassified
“…69 Two trials reported a possible association between high concentration of voriconazole and neurologic adverse events. 31,29 Pascual and others 29 recorded neurologic events (including confusion, agitation, pattern of toxic encephalopathy on electroencephalography, extrapyramidal signs, myoclonus, and visual and auditory hallucinations) in 5 of the 16 patients who had trough concentrations of voriconazole above 5.5 mg/L; they observed no such effects in the group with concentrations of 5.5 mg/L or below (p = 0.002). In a small retrospective study, 4 of 6 patients with neurologic adverse events (including neuropathy, hallucinations, anxiety, insomnia, irritability, and impaired concentration) had trough concentrations of voriconazole above 4 mg/L.…”
Section: Relation Between Concentration and Toxic Effectsmentioning
confidence: 99%
“…8, [25][26][27][28][29][30][31][32] In their recent review articles, Smith and others 33 and Hope and others 34 addressed the topic of TDM for antifungal agents, discussing voriconazole briefly. Brüggemann and others 35 and Howard and others 36 also discussed the role of TDM for voriconazole specifically, the latter focusing exclusively on invasive aspergillosis.…”
mentioning
confidence: 99%
“…Finally, posaconazole absorption is saturable, thus despite a long elimination half life, exposure is increased when administered as divided doses of 200 mg four times daily versus as a single 800 mg daily dose 41,42 . Interpatient variability with voriconazole is primarily due to differences in metabolism related to CYP2C19 polymorphisms, rather than absorption issues, although voriconazole absorption is modestly reduced by administration with food 43 . CYP2C19 is the major determinant of voriconazole metabolism and clearance, and patients who are homozygous extensive CYP2C19 metabolizers have markedly lower plasma concentrations than homozygous poor metabolizers or heterozygous extensive metabolizers 44,45 .…”
Section: Pharmacokinetics (Pk) and Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%